Wartime activities of the Vavilov Institute - I. G. Loskutov (Труды по прикладной ботанике, генетике и селекции)
Among the chronicles relating the heroism of the besieged Leningrad, there are pages dedicated to the deeds performed by the staff the world-famous All-Union Research Institute of Plant Industry (VIR, now the N.I. Vavilov All-Russian Institute of Plant Genetic Resources). With the beginning of the war, even before the city was surrounded by the Nazi troops, the government decided to evacuate a number of factories and institutes from Leningrad, including VIR, but the plan failed. Only in winter did the Institute start partial evacuation, although preparations had been going on for a long time. The largest and most important part of the collection was left behind in the besieged city. The remaining employees were forced to work under the hardest conditions of the siege, in unheated premises. In the harsh reality of the winter in 1941–1942, the daily bread rationing was cut down, and hunger raged in the city, killing tens of thousands of city residents, including VIR employees who kept the stored seeds and tubers untouched. The most difficult part was preserving the potato collection. In the spring of 1942, preparations were made for sowing to restore the viability of seeds and tubers in the fields of Leningrad’s suburban area under the fire from the enemy artillery. Only the heroic efforts of VIR’s staff helped to save the collection from destruction and loss of germination. This heroism cost more than 20 experts and scientists their lives. So, the most dangerous period for the Institute was overcome at such price. Immediately after the siege was lifted, a group of experts was sent to Leningrad from Krasnoufimsk to help with selecting seed accessions for urgent reproduction. Working under extreme physical exhaustion in frozen premises, without water or electricity, under continuous shelling, they saved, many at the cost of their own lives, the collection of cultivated plants and their wild relatives, the herbarium, and the scientific library for future generations.